TREAT: systematic and inclusive selection process of genes for genomic newborn screening as part of the Screen4Care project - Christina Saier; Stefaan Sansen; Joanne Berghout; Kathrin Freyler; Moshe Einhorn; Yaron Einhorn; Leslie Matalonga; Sergi Beltran; Antonio Novelli; Rita Selvatici; Fernanda Fortunato; Silvia Montanari; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Genomic newborn screening (gNBS) offers the potential to detect genetic conditions early, enhancing outcomes through timely treatment. It can serve as an additional tool to identify conditions that are not detectable via metabolic screening. The Screen4Care project seeks to develop a systematic approach for selecting treatable rare diseases (RDs) for inclusion in gNBS through the creation of the TREAT-panel. Methods A set of six selection criteria containing treatability, clinical validity, age of onset, disease severity, penetrance, and genetic feasibility was applied to a comprehensive list of gene-disease pairs. Genes meeting a defined threshold score were included in the TREAT-panel. This automated scoring process was complemented by expert review from clinicians and patient representatives to ensure clinical relevance and adherence to current medical guidelines. Results The initial gene list, derived from multiple data sources, included 484 gene-disease pairs. After applying the scoring system and two rounds of expert curation, a final list of 245 genes was selected. These genes predominantly represent disorders in metabolic, neurological, and immunological categories, with treatability and early disease onset as key inclusion factors. Conclusion The Screen4Care TREAT-panel provides a curated, scientifically robust gene set for gNBS, focusing on treatable RDs with early onset and clinical actionability. The panel will be tested in a European pilot project involving approximately 20,000 newborns, contributing to the growing body of evidence for the implementation of next-generation sequencing (NGS) in newborn screening programs.